Dysphemism in eating expressions in Javanese: A study of cognitive semantics - Hermandra Hermandra; Elvi Citraresmana; Anida Sarudin; Hasmidar Hassan (Universitas Syiah Kuala, 2024)
The word eating can produce positive meaning as it is closely tied to human needs. This term is also intricately linked to eating habits. In Javanese society, this term serves to satisfy basic human needs and plays a pivotal role in defining social etiquette. Eating expressions have a broader meaning when examined from a dysphemistic perspective within cognitive semantics. This study employed a descriptive qualitative methodology, with data collection covering interviews, active listening, observation, and note-taking. The data were then analyzed using image schemas and conceptual meaning. The study found that the eating expressions underwent dysphemism in Javanese such as lambene ngemrus wae ket mau! (your mouth keeps eating!), wes, ngrokoti koyo tikus! (you eat like a rat!), Gimin esuk-esuk wis nguntal (Gimin ate too early this morning), wah, yahene wis nyekek ping pindho (you have eaten twice by this time), nyo, badhogen kabeh, aku rasah dingengehi (eat all the food and dont bother to spare for me), panganan kok di gaglak (how come you gulping the food?), and menungso kok gragas?! (how on earth could you only eat?!). Moreover, the study identified conceptual metaphors, comprising six structural metaphors and two orientational metaphors. Structural metaphors arise from systematic relationships observed in daily experiences, whereas orientational metaphors impart spatial direction, including the recognition of top-down image schemes, part-whole image schemes, existence image schemes, and merging image schemes.